Pitch patterns of Mongolian compound place names - Ueta, Naoki (Acta Mongolica, 2014)
Mongolian accent is not distinctive in relation to meaning. With respect to Mongolian accent, not a few researches have been carried out, including studies which claim that Mongolian has stress accent (Hangin1968), pitch accent (Kakudo 1982) and both of them (Ozawa 1994). In recent research Karlsson (2005) clarified the pitch patterns of Khalkha Mongolian, taking the position that Mongolian has no lexical stress. However, the accent of compound words in Mongolian has not been clarified well so far. In this study, pitch patterns of Mongolian compound place names which consist of two words, such as Ʊlaan-baatar and bɔr-nƱƱr, are analyzed, and it is clarified that 1) most compound place names are pronounced not as two words but as a single phonological word, 2) in general the word accent of the first element is preserved and that of the second element disappears, and 3) in some words, the number of syllables, vowel length and syllable structure are related to the pitch pattern.